A resource unit in testing for biology teachers in secondary schools - Mamaril, Lorenza D. (Quezon City [publisher not identified], 1973)
This material was developed to encourage biology teachers to prepare better quality tests of achievement. It sought to carry out this aim by establishing a strong foundation in testing through a knowledge of principles of test construction and basic procedures in the preparation of classroom tests. The techniques of testing emphasized in this paper are those pertaining to planning, preparation, and analysis of tests items.
Thesis (Master of Arts in Teaching (Biology))--University of the Philippines.
Keywords: Biology -- Examinations